2020
DOI: 10.14710/jiab.2020.28102
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Produk Makanan, Harga, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Rm. Rindang 84 (Studi Pada Konsumen Rm. Rindang 84 Cabang Pati)

Abstract: Business in the culinary field is now a promising choice when looking at the level of mobility of everyone who tends to choose practicality in meeting the needs of eating or drinking. Establish a restaurant like Rindang 84 became one of the choices that could be made. The key to successfully running a culinary business in order to survive is to be able to produce and offer products or services that are tailored to the needs that pay attention to elements such as food product quality, prices, and service qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
1
0
4
Order By: Relevance
“…Other studies also indicate that product quality has a positive influence on purchase decisions for Wall's ice cream in Sidoarjo City (Ugy & Boggy Nugraha, 2023). Cahyani & Hidayat (2020) study also revealed a significant influence between food product quality and purchase decisions at Rindang 84 restaurant branches in Pati, with the majority of respondents stating that the food product quality at Rindang 84 restaurant is of good quality.…”
Section: The Influence Of Product Quality On Purchase Decisionmentioning
confidence: 71%
“…Other studies also indicate that product quality has a positive influence on purchase decisions for Wall's ice cream in Sidoarjo City (Ugy & Boggy Nugraha, 2023). Cahyani & Hidayat (2020) study also revealed a significant influence between food product quality and purchase decisions at Rindang 84 restaurant branches in Pati, with the majority of respondents stating that the food product quality at Rindang 84 restaurant is of good quality.…”
Section: The Influence Of Product Quality On Purchase Decisionmentioning
confidence: 71%
“…Keputusan pembelian mie instan ini harusnya tak hanya tergantung simbol atau merek dari produk namun juga berdasarkan tingkat religiusitas pembeli karena religiusitas seseorang sangat menentukan keputusan apa pun yang dibuat termasuk pembelian (Rahman 2022). Berdasarkan pada penelitian (Cahyani and Hidayat 2020) (Auliyana 2020) menyampaikan bahwa keputusan pembelian dipengaruhi brand image dan kualitas produk, (Agustino and Syaifullah 2020) (Nurhayati, Hasanuddin, and Suyandi 2022) menambahkan kepercayaan dan kualitas informasi juga berpengaruh, ditambah oleh (Rahayu 2021) (Alfatiha and Budiatmo 2020) harga juga mempengaruhi keputusan pembelian, pada penelitian (Siswanty and Prihatini 2020) dipaparkan penggabungan dari penelitian sebelumnya. ) memaparkan pengaruh maqashid syariah dan label pada keputusan pembelian, ini pun sejalan dengan pemaparan (Fasya and Rahwana 2021).…”
Section: Pendahuluanunclassified
“…Perkembangan bisnis pada era ini memiliki kemajuan yang semakin pesat, ditandai dengan semakin banyak berdirinya usaha bisnis dalam berbagai produk, salah satunya bisnis kuliner yang saat ini menjadi pilihan bagi banyak orang, karena mengingat semakin tingginya aktivitas dan mobilitas orang yang menjadikan peluang besar untuk menarik konsumen dan melakukan pembelian (Cahyani & Hidayat, 2020) Seiring dengan kemajuan peradaban manusia dan datangnya era globalisasi, perkembangan teknologi dibidang komunikasi dan informasi mengalami peningkatan dengan pesatnya. Salah satu bentuk media informasi yang dikenal dan melekat pada masyarakat adalah surat kabar (Tulandi Riry.…”
Section: Pendahuluanunclassified